Pengaruh Pakan Buatan Terhadap Perkembangan dan Produksi Madu Apis Mellifera L. - Sahetapy, Max (JIU (Jurnal Ilmiah Unklab); Volume 3 No. 1, 2000 JIU UNKLAB, 2000)
The supply of nectar and pollen as natural food for honey bee has been a problem for honey bee farmers due to its high dependence on climate, seasons, plant species, and blooming seasons. This research was intended to investigate whether artificial food could become an alternative food for honey bee. With the use od treatment consisting of 6 (six) kinds of mixed measurements of cane sugar, palm sugar, water, and yolk, the experiment results showed that the use of artificial food significantly increased the number of honey bee cells, the behavior of the colony, the color and the quality of the honey. It had no effects on the life stadium and on the quantity of the honey considerably.